Stages of Mechanochemical Depolymerization of Poly(styrene) Powder in Oxidative and Inert Atmospheres - Chang, Yuchen; Hergesell, Adrian H; Seitzinger, Claire L; Hepstall, Aubrey M; Vollmer, Ina; Sievers, Carsten (ACS sustainable chemistry & engineering, 2025)
Mechanochemical depolymerization of poly-(styrene) can yield its monomer styrene, but insufficient kinetic and mechanistic insight hamper productivity and efficient reactor design. Herein, ball milling of poly-(styrene) powder in a continuous flow reactor is coupled with real-time measurement of the rate of formation of individual products using in-line gas chromatography, complemented by multitechnique characterization of poly-(styrene) residue at specific time points including electron spin resonance, size exclusion chromatography, nuclear magnetic resonance spectroscopy and thermogravimetric analyses. Using this approach, three distinct stages in the depolymerization reactions are revealed, characterized by successive dominance of surface creation, surface friction and finally a molecular weight limit as the determining factor in the rate of styrene production. By comparing instantaneous product formation rates and trends in radical abundance under air and nitrogen atmospheres, oxygen is shown to be a promoter of depolymerization reactions through oxidation of polymer radical intermediates as well as a suppressor of radical migration. Minor coke formation is due to radical transfer reactions. Although conversion is nonquantitative, our study provides detailed mechanistic insights to overcome kinetic bottlenecks.